Transforming Healthcare: Integrating Clinical, Administrative, and Emergency Services - Abdulaziz Jaber Alhashel, Basem Saud Abdullah Alghamdi, Hussain Muteb Jaber Harise, Mohammed Ahmed Ibrahim Al-Hazmi, Hussam Mohsen Mashuof, Ibrahim Ismail Hamaml, Abdul Aziz Abdo Ali Agili; Marwah Mohammed Nasser, Zakia Abdelmalek Alhothali, Sarah Ahmed Aljehani, Amaal Muhammed Althomali, Sara Atiah Alharthi (Journal of International Crisis and Risk Communication Research, 2024)
Most of the agencies involved in the process of healthcare services and the respective stakeholders are looking of the positive changes in the processes and policies to update the current services and provide funds and equipment to deal with the chronic ailments at present and in future. In a developing country like Saudi Arabia this is somewhat difficult as the government has just started to look after the service in recent past i.e. since 2010 and onward. This shows that there is great scop of improvement in the healthcare related services. At the same time the policy makers have taken corrective actions and measures to take the system to a new level. In the present time choice of patient and competition among the health care providers have shifted the overall system to a new level, this called for the increasing importance of integration in the field of healthcare services. However, such a scenario is hidden in the layers of future sky and may emerge at a given point of time, also the stakeholders may find ways and means to deal with the same. This Present study will focus on the integration of healthcare services in the country and present a details review of the process. some part of the study is based on primary data as well to get the better insight of the scenario.